2001
DOI: 10.1177/152700250100200106
|View full text |Cite
|
Sign up to set email alerts
|

Is the Reward System in NASCAR Efficient?

Abstract: This article provides an overview of compensation and reward schemes in professional automobile racing (NASCAR). Data from the 1998 and 1999 racing seasons show that although end-of-season rewards are highly nonlinear, individual races offer rewards that are more linear. Given that the general conditions for a rank order tournament do exist, this may indicate that the reward scheme is inefficient. Several hypotheses are suggested to explain why NASCAR would create such a reward structure. Vital to the investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The idea is that the more effort is supplied by drivers, the greater the potential for an accident, which would lead to a caution flag. This concept is closely related to the sabotage incentive posited by von Allmen (2001). If the number of caution flags is correlated with the unobservable error term, then the OLS estimator used here is neither unbiased nor consistent.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The idea is that the more effort is supplied by drivers, the greater the potential for an accident, which would lead to a caution flag. This concept is closely related to the sabotage incentive posited by von Allmen (2001). If the number of caution flags is correlated with the unobservable error term, then the OLS estimator used here is neither unbiased nor consistent.…”
Section: Discussionmentioning
confidence: 98%
“…von Allmen (2001) posited that other alternative models could be applied to NASCAR race outcomes, documenting a number of features of NASCAR races that differ from other sporting events. NASCAR drivers compete for three types of awards in each race: cash winnings based on rank order of finish in the race, points that accrue over the course of the season and count toward a season-long competition with a sizable monetary reward to the driver who accumulates the most points over the course of the season, and other bonus payments for in-race accomplishments like the number of laps lead or winning the pole position in the race.…”
Section: Predictions and Tests Of Tournament Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have examined the specific nature of NASCAR’s rank-order tournament system. An influential article by von Allmen (2001) presented a theoretical argument for why a nonlinear reward structure for monetary payouts from races and championship points would be inefficient in NASCAR. 6 His sponsorship hypothesis suggested that drivers already had a strong incentive to favor a risk-averse strategy because drivers would not risk getting involved in an accident for a small amount of additional prize money if sponsors had a strong dislike for accidents and poor finishes.…”
Section: Literature Reviewmentioning
confidence: 99%